Malignant Syphilis in HIV: A Diagnostic and Management Challenge - Regina, Senduk Cindy; Niode, Nurdjannah Jane (Heca Sentra Analitika, 2025)
Malignant syphilis is a rare and severe form of secondary syphilis, often seen in immunocompromised individuals, including those with advanced HIV infection. We report a 29-year-old male with newly diagnosed Stage IV HIV who presented with widespread erythematous plaques and scales and systemic symptoms. Dermatological examination revealed generalized erythematous macules and plaques with scaling, erosion, and crusting. Ulcerative lesions with crusts were noted on the toes and soles. Venereological findings included erythematous to skin-colored macules on the scrotal and penile areas. Serological tests revealed high VDRL (1:128) and TPHA (>1:5120) titers, and histopathology confirmed secondary syphilis. The patient was treated with intramuscular benzathine penicillin G (2.4 million units) weekly for three weeks in conjunction with antiretroviral therapy (ART). Although the patient experienced a Jarisch-Herxheimer reaction, there was significant clinical and serological improvement, with a fourfold reduction in VDRL titers after nine months. This case emphasizes the need for early recognition of malignant syphilis in immunocompromised patients and highlights the effectiveness of benzathine penicillin G and ART in treatment. Regular follow-up is essential to monitor progress and prevent recurrence.